2011
DOI: 10.3945/ajcn.111.018143
|View full text |Cite
|
Sign up to set email alerts
|

Zinc absorption and zinc status are reduced after Roux-en-Y gastric bypass: a randomized study using 2 supplements

Abstract: Background: Micronutrient deficiencies are common in patients undergoing gastric bypass. The effect of this type of surgery on zinc absorption and zinc status is not well known. Objective: The objective was to evaluate the effects of Roux-en-Y gastric bypass (RYGBP) on zinc status and zinc absorption at different stages after surgery. We hypothesized that zinc status would be significantly impaired after surgery and that this impairment would be less severe in subjects receiving increased supplemental zinc. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 51 publications
3
47
0
8
Order By: Relevance
“…Authors suggested that this indicated an impairment in Zn absorption after RYGB. Ruz [15] et al confirmed that Z significantly impaired soon after RYGB and this persists at least until 18 months after surgery. In this study percentage Zn absorption decreased from 32.3 % before surgery to 13.6 % by 6 months after surgery.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Authors suggested that this indicated an impairment in Zn absorption after RYGB. Ruz [15] et al confirmed that Z significantly impaired soon after RYGB and this persists at least until 18 months after surgery. In this study percentage Zn absorption decreased from 32.3 % before surgery to 13.6 % by 6 months after surgery.…”
Section: Resultsmentioning
confidence: 76%
“…It is also evident that RYGB leads to not just a reduction in intake of Zn [15][16] but also its absorption [15,19]. In the study by Ruz et al [15], dietary Zn intake was 9.1, 5.4, 6.4, and 7.2 mg/d before and 6, 12, and 18 months respectively after RYGB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations